2012ネン ナンキョク イガク イリョウ ワークショップ ホウコク - 大野, 義一朗; オオノ, ギイチロウ; 渡邉, 研太郎; ワタナベ, ケンタロウ; Ohno, Giichiro; Watanabe, Kentaro (2013)
P(論文) 2012 年の南極医学医療ワークショップが7月28日,国立極地研究所で開催された.このワークショップは,日本の南極地域観測での医学・医療の成果を報告し,同時に次期の医学研究計画の立案を支援することを目的として,2004年から毎年開催されている.今年は30施設から37人の参加者があり,南極医学の多様な問題,南極現場での医療に関して14演題の報告がなされた. 2006年からは南極観測にかかわる中国,インド,韓国の医学・医療担当者の参加を得ており,今年も中国,韓国からの報告があった.本ワークショップは南極医学研究および医療に関し,アジアにおける重要なネットワークとして機能しており,情報交換および議論を通して南極医学研究および医療での発展が期待できる.本報告ではそれぞれの報告の要旨を掲載する. The "Workshop on Antarctic Medical Research and Medicine 2012" was held on 28 July 2012 at the National Institute of Polar Research, Tokyo, Japan. This workshop has been held annually since 2004 to present results from medical research and operational medicine conducted by the Japanese Antarctic Research Expedition (JARE) and to discuss medical research programs for the next expedition team. Thirty-seven participants from 30 institutes contributed to the workshop. There were 14 presentations concerning various aspects of Antarctic medical research and practical medicine. Antarctic medical doctors from China, India, and Korea have also participated in this workshop since 2006. Chinese and Korean medical doctors who will be members of the next wintering team reported on their countries' Antarctic medical activities of this year. This workshop plays an important role as a local Asian network for Antarctic medical research and medicine. It is expected that the workshop will stimulate and encourage participating researchers to develop Antarctic medical research projects and medicine through the exchange of information and discussion. This article summarizes the collected abstracts from the workshop. departmental bulletin paper